Common shocks and relative compensation schemes - Michael Magill; Martine Quinzii (University of California, Department of Economics, 2004)
This paper studies qualitative properties of an optimal contract in a multi-agent setting in which agents are subject to a common shock. We derive a necessary and sufficient condition for the optimal reward of an agent to be a decreasing (increasing) function of the outputs of the other agents, under the assumption that the agents' outputs are informative signals of the value of the common shock. The condition is that the likelihood ratio of a given outcome with high versus low effort be a decreasing (increasing) function of the common shock. We derive conditions on the way the common shock affects the marginal product of effort under which the likelihood ratio is decreasing for all output levels, or increasing for some output levels and decreasing for others.
Keywords: 330